ANALISA PASANGAN JEMBATAN GARAM RESIDU GLU15-LYS4 PADA KESTABILAN TERMAL PROTEIN 1GB1 - kania N Sawitri (Jurnal Biofisika, 2014)
Simulation on protein G domain B1 (1GB1) have been performed using NAMD2. This protein is well-known for its high termal stability (melting point about 363 K) and attract many scientists to study it. The aim of this research is to study the effect of mutation on salt-bridge pairs GLU15-LYS4 to the thermal stability of 1GB1 protein. The pair was chosen based on simulation analysis for native structure (wild-type) in which non-binding energy towards zero when unfolding occurred (t=678 ps). Mutations were done by interchanging the position of the pair, neutralizing one of the residue, and neutralizing both residues in the pair. This research is focused on observing the changes caused by the mutations without paying attention to the change of protein function. The results show that neutralizing GLU15 to ASN 15 would increase the thermal stability which indicated by longer unfolding time at 820 ps.